A current model for training a pulmonologist - A G Chuchalin (Терапевтический архив, 2013)
The paper gives data on the importance of the results of genomic and postgenomic studies and the wide practical introduction of up-to-date diagnostic imaging techniques for improving the scientific and practical branches of modern pulmonology. Great attention is paid to the initiative of the European Respiratory Society for harmonized education in respiratory medicine and for improvement of the knowledge and skills of entry-level specialists.